Venous thromboembolism prevention protocol for adapting prophylaxis recommendations to the potential risk post total knee replacement: a randomized controlled trial - Mariam A. Alameri; Syed A. Syed Sulaiman; Abdullah M. Ashour; Ma'ad F. Al-Saati (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Background: Total knee replacement (TKR) is a major orthopedic surgery that is considered high risk for the development of venous thromboembolism (VTE). Objective: The aim of this study is to evaluate the clinical outcomes that resulted from the use of a new proposed VTE risk stratification protocol for selecting a suitable extended VTE prophylaxis for post TKR surgery patients administered in conjunction with patient education programs. Method: A randomized controlled trial was conducted in two medical centers in Saudi Arabia. A total of 242 patients were enrolled in the study, 121 patients in each group. The experimental group (A) was assessed by using the proposed VTE risk stratification protocol and also took part in patient education programs about TKR and its complications. The control group (B) was assessed by using the 2005 Caprini risk assessment tool and no education programs were given to this group. Both groups were followed for 35 days post operation. Results: The mean age of the participants was 65.86 (SD 8.67) and the majority of them were female 137 (56.6%). The mean body mass index of the study sample was 32.46 (SD 5.51). There were no significant differences between the two groups except for surgery type; the proportion of bilateral TKR in group A was higher than in group B (69/121 (28.5%) vs. 40/121(16.5%), p˂0.05). There were no confirmed pulmonary embolism cases in the study sample and diagnosis of deep-vein thrombosis was confirmed in 12/242 (5.0%) of patients: 1/121 (0.8%) in group A and 11/121 (9.1%) in group B (p˂0.05). The readmission rate for all patients was 2.5% (6/242), all of whom were in group B (p˂0.05). Conclusion: The proposed VTE risk stratification protocol that was applied in conjunction with patient education programs reduced VTE complications and readmission events, post TKR surgery. Trial Registration: ClinicalTrials.gov Identifier: NCT04031859.